2017
DOI: 10.3390/ijms18030592
|View full text |Cite
|
Sign up to set email alerts
|

Potential Neuroprotective Effects of Adiponectin in Alzheimer’s Disease

Abstract: Abstract:The adipocyte-secreted protein adiponectin (APN) has several protective functions in the peripheral tissues including insulin sensitizing, anti-inflammatory and anti-oxidative effects that may benefit neurodegenerative diseases such as Alzheimer's disease (AD). In addition, dysregulation of cerebral insulin sensitivities and signaling activities have been implicated in AD. Emerging insights into the mechanistic roles of adiponectin and AD highlight the potential therapeutic effects for AD through insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 93 publications
1
60
1
1
Order By: Relevance
“…Insulin signaling in the brain reportedly regulates key processes, including neuronal growth, synaptic plasticity, and energy homeostasis [70], and the disruption of insulin signaling is recognized as an important risk factor for AD pathogenesis [50,71]. Noticeably, APN has been reported to have insulin-sensitizing and anti-inflammatory actions [72] by activating multiple signaling molecules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insulin signaling in the brain reportedly regulates key processes, including neuronal growth, synaptic plasticity, and energy homeostasis [70], and the disruption of insulin signaling is recognized as an important risk factor for AD pathogenesis [50,71]. Noticeably, APN has been reported to have insulin-sensitizing and anti-inflammatory actions [72] by activating multiple signaling molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these findings indicated that HFDinduced oxidative stress mediates neuronal insulin resistance by impairing adipoR1/p-AMPK signaling both in vivo and in vitro. Previous studies have reported that, under physiological conditions, adiponectin (APN), through phosphorylation of adiponectin receptor 1 (AdipoR1), activates AMPK, and regulates insulin signaling in the brain [2,50]. However, HFD-induced obesity results in peripheral metabolic changes and significant reductions in AMPK levels in the brain [12,51].…”
Section: Hfd Induces Oxidative-stress-mediated Brain Insulin Resistanmentioning
confidence: 99%
“…Adiponectin enters the brain from circulation and directly targets neurons (Ng and Chan 2017; Thundyil et al 2012; D. Zhang et al 2016; Zhang et al 2017; Song et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Given this broad distribution of adiponectin receptors in different brain regions, adiponectin’s role may be broader than the regulation of metabolic homeostasis and could plan an important role in the ‘adipocyte-brain cross-talk’ (Thundyil et al 2012). Adiponectin is involved in neurogenesis, dendritic spine remodeling, hippocampal neural stem cell proliferation and dentate gyrus neuronal excitability (Zhang et al 2017; Ng and Chan 2017; Song et al 2015; D. Zhang et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation